Effect of Governance on the Efficiency of the Indonesian Banking Industry - Indrianti, Fransiska Novina Hayu; T., Sutrisno; Saraswati, Erwin (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
This study aims to examine observations and determine the effects of corporate governance on the efficiency of the Indonesian banking sector. The research calculated DEA efficiency and performed logistic regression, with a total sample of 150 observations. Results show that independent commissioners, the educational level of commissioners, the board of commissioners meeting, and the term of office of the commissioners all have a significant impact on improving the efficiency of the banking industry. Conversely, the large number of commissioners as well as the gender differences among them do not have any effect on banking efficiency. These findings indicate that authorities should not focus on the size of the board and the gender differences among the board commissioners in finding ways to increase or decrease a firm’s efficiency. The results of this study can contribute to academic research through agency theory and resource dependence theory as well as provide insights that can be used by practitioners. Keywords:  Governance; banking efficiency; DEA